Using your chemistry :Comprehension Questions for Advanced Level - Scott, P.R. ([S.l.] : Nelson Thornes Ltd, 1990)
A-level chemistry questions increasingly test the students ability to handle unfamiliar situations, and prove that they can apply their knowledge. This is a book of comprehension questions, ranging from familiar extension material to completely new topics. It is written in response to the need for candidates to have experience of these types of questions before they sit their examination. The material is suitable for A-level, Scottish Higher and Certificate of Sixth Year Studies. An answer book is also available.
Keywords: chemistry